Exploration of automation of laboratory testing and management - Huifang WANG (Dianxin kexue)
Laboratory testing is a high technical work and need to obey lots strict requirements in all aspects to ensure the accuracy of the work.In order to ensure the quality of laboratory work and improve the efficiency of work,laboratory testing and management system was explored and completed.The system improved the efficiency of the work,completed a large amount of repeated artificial work and reduced the error rate of the detection.Based on this,a test database was formed and a variety of functions were expanded.